Concentration-dependent activity coefficients of lanthanides in liquid bismuth for the FHR primary coolant cleanup. (March 2018) - Wang, Yafei; Zhou, Wentao; Guo, Shaoqiang; Zhang, Jinsuo
Highlights: The activity coefficients of lanthanides for the concentration up to solubility limit were obtained. The activity coefficients of lanthanides over a wide range of temperature were provided. The temperature- and concentration-dependent correlations of the activity coefficients were developed. Abstract: The activity coefficients of lanthanides in liquid bismuth at different concentrations and temperatures were calculated based on the assessed expression of Gibbs energy by the method of CALPHAD (CALculation of PHAse Diagrams). The temperature- and concentration-dependent correlations of the activity coefficients of eight lanthanides were developed which make it possible to calculate the activity coefficient for any concentration up to the solubility limit in the temperature range of 873–973 K. Based on the correlations developed, the change of the activity with concentration was analyzed and discussed. This research provided calculated fundamental properties of lanthanides in liquid bismuth over a wide range of concentration and temperature for the FHR primary coolant cleanup system development. The method used in this study can be extended to investigate other liquid metal binary or ternary systems.